Helix‐sense‐selective copolymerization of triphenylmethyl methacrylate with chiral 2‐isopropenyl‐4‐phenyl‐2‐oxazoline. Issue 3 (19th September 2018) - Shen, Jun; Ikeda, Naoto; Bi, Wanying; Satoh, Kotaro; Kamigaito, Masami; Okamoto, Yoshio
ABSTRACT: The asymmetric induction leading to a one‐handed helix was investigated in the anionic and radical copolymerization of triphenylmethyl methacrylate (TrMA) and ( S )‐2‐isopropenyl‐4‐phenyl‐2‐oxazoline (( S )‐IPO), and highly isotactic copolymers with a reasonable optical activity were obtained. In the anionic copolymerization, the optical activity of the obtained copolymers depended on the polarity of solvents, and a highly optically active copolymer was produced in the copolymerization in toluene. The chiral oxazoline monomer functioned not only as a comonomer but also as a chiral ligand to endow the polymer with large negative optical rotation in the copolymerization with TrMA. The copolymers with small positive optical rotation were obtained in THF, indicating that IPO unit may work only as the chiral monomer that dictates the helical sense via copolymerization with TrMA. The isotacticity of the obtained copolymers depended on the contents of TrMA units in the copolymers, but was almost independent of the solvent for copolymerization. In the radical copolymerization, the obtained copolymers exhibited small optical activities. It seemed that the chiral monomer cannot induce one‐handed helical structure of TrMA sequences even if the sequences probably have a high isotacticity. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 441–447 Abstract : The asymmetric induction leading to a one‐handed helix was investigated in the anionic and radical copolymerization of triphenylmethyl methacrylate and ( S )‐2‐isopropenyl‐4‐phenyl‐2‐oxazoline. Helical copolymers were successfully obtained in the anionic copolymerization, while no helicity induction occurred in the radical system. The optical activity of the anionically obtained copolymers was dependent on the polarity of solvent (toluene and THF), and toluene was the solvent of choice to induce the desired optical activity of the copolymer.